Graphene/Half‐Metallic Heusler Alloy: A Novel Heterostructure toward High‐Performance Graphene Spintronic Devices. Issue 6 (3rd December 2019) - Li, Songtian; Larionov, Konstantin V.; Popov, Zakhar I.; Watanabe, Takahiro; Amemiya, Kenta; Entani, Shiro; Avramov, Pavel V.; Sakuraba, Yuya; Naramoto, Hiroshi; Sorokin, Pavel B.; Sakai, Seiji
Abstract: Graphene‐based vertical spin valves (SVs) are expected to offer a large magnetoresistance effect without impairing the electrical conductivity, which can pave the way for the next generation of high‐speed and low‐power‐consumption storage and memory technologies. However, the graphene‐based vertical SV has failed to prove its competence due to the lack of a graphene/ferromagnet heterostructure, which can provide highly efficient spin transport. Herein, the synthesis and spin‐dependent electronic properties of a novel heterostructure consisting of single‐layer graphene (SLG) and a half‐metallic Co2 Fe(Ge0.5 Ga0.5 ) (CFGG) Heusler alloy ferromagnet are reported. The growth of high‐quality SLG with complete coverage by ultrahigh‐vacuum chemical vapor deposition on a magnetron‐sputtered single‐crystalline CFGG thin film is demonstrated. The quasi‐free‐standing nature of SLG and robust magnetism of CFGG at the SLG/CFGG interface are revealed through depth‐resolved X‐ray magnetic circular dichroism spectroscopy. Density functional theory (DFT) calculation results indicate that the inherent electronic properties of SLG and CFGG such as the linear Dirac band and half‐metallic band structure are preserved in the vicinity of the interface. These exciting findings suggest that the SLG/CFGG heterostructure possesses distinctive advantages over other reported graphene/ferromagnet heterostructures, for realizing effective transport of highly spin‐polarized electrons in graphene‐based vertical SV and other advanced spintronic devices. Abstract : A novel heterostructure consisting of high‐quality single‐layer graphene (SLG) and a half‐metallic Heusler alloy Co2 Fe(Ge0.5 Ga0.5 ) (CFGG) is developed. This new heterostructure shows unusual weak interfacial interaction, which leads to distinctive features such as preservation of the robust magnetism and half‐metallic characteristic of CFGG near the interface, and the quasi‐free‐standing nature of SLG, providing a new platform for future development of advanced graphene spintronic devices.